As três moedas (Trinummus) - Reina Marisol Troca Pereira (Autores Gregos e Latinos - Ensaios, 2014)
Trinummus is another fabula palliata by Plautus. Enriched by the art of the Latin author, the result was too tedious and very elitist, compared to what usually characterized the Plautine comic. Through stock characters of fixed social types (e.g. the old, the Young, the slaves), several cultural themes are analyzed, such as friendship, morality, loyalty, money. Thus, the senex Charmides, whose assets were in danger because of the conduct of his son, Lesbonicus, leaves Athens. Meanwhile, his young son and daughter were trusted to his friend Callicles, as well as his house. Secretly, Callicles told Charmides about the treasure buried in his home. However, Charmides was in a dilemma, between keeping the secret of his friend and avoiding the dissolute spirit of Lesbonicus. Using his father's journey to his own profit, the youngster put the house for sale. Therefore, Callicles felt the moral obligation of purchasing it. Lisiteles involuntarily made the situation worse, because of his intention to marry Lesbonicus' sister. The proposal required a dowry, which constituted a problem to Lesbonicus and to Callicles. This senior, wrongly judged both socially (cf. Megaronides), and privately (cf. Charmides, who had returned from his trip), was finally thanked and praised, when all the facts were acknowledged.